METODE DAKWAH SILAHTURAHMI KE RUMAH WARGA OLEH PENDAKWAH MUALAF - Noval Setiawan (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2020)
Abstract Da'wah is an activity to invite someone to the way of Allah. A preacher must certainly have a method of preaching what will be applied in an area, especially in that area, the people adhere to Islam, Christianity and Hinduism. This study aims to determine how the da'wah and the response of the community to the da'wah methods applied by new converts in multi-religious communities. The type of research method used in this research is qualitative research. The use of this method is intended to be able to reveal and explain the phenomena that occur and also more fully and deeply. The location of this research is in the village of Anggrasmanis, Jenawi District, Karanganyar Regency, Surakarta. The results of this study are the da'wah method used by the new Muslim preacher named Mr. Samsudi, namely applying the silahturahmi method to visit residents' homes to invite the Anggrasmanis village community to pray in congregation in mosques and embrace Islam. This da'wah method was carried out for five years and often received negative responses from the community. Keywords: Da'wah, Silahturahmi, Preaching Converts.